Computed tomography exam of the thorax of female dogs with malignant mammary gland tumors: II - Pulmonary parenchimal evaluation - Pinto, Ana Carolina Brandão de Campos Fonseca; Iwasaki, Masao; Figueiredo, Cláudia Maria de; Cortopassi, Sílvia Renata Gaido; Sterman, Franklin de Almeida (Brazilian Journal of Veterinary Research and Animal Science, 2007)
Seen the importancy of the malignant mammary gland tumors in the veterinary medicine clinic, the new perspectives of the diagnostic imaging in order to evaluate pacients that have this neoplasia, and the few information of this subject in the literature this research proposed to compare contrast computed tomographic and survey radiographic techniques in the lung's evaluation of female dogs with malignant mammary gland tumors. This research was performed at the Diagnostic Imaging Service of the Veterinary School Hospital of the Faculdade de Medicina Veterinária e Zootecnia at the University of São Paulo in twenty, from different breed and age, bitches with malignant mammary gland tumors that were examined at the Obstetric and Ginecology and Small Animal Surgery Services of the same hospital. The tomographic exam showed up as an important complement of the radiographic exam in searching for mammary gland tumor metastasis, concerning the evaluation of the pulmonary intersticium.